Global Warming From Ethical View - Daniel Sudibyo Tjandra (Budapest International Research and Critics University, 2022)
This article contains a hot issue in the world's view, where global warming is a significant problem for all countries. Examines in detail the problem of global warming by using a descriptive approach to become a conceptual framework that then becomes simultaneous handling of ecological issues from the point of view of Christian ethics. It is hoped that humans can actively participate in caring for the environment and the Universe.